An integral equation approach to heat and mass transfer problem in an infinite cylinder - Tripathi G.; Shukla K.N.; Pandey R.N. (My University, 2025)
In this paper the authors have developed a method of integral equations to obtain the transfer potentials for heat and mass in a body of unidimensional infinite cylinder under the influence of the most general type of boundary conditions. An approximate solution, applicable for small values of generalized time has also been worked out for the system. © 1973.